Investigating The Effect of Artificial Intelligence Based Tools on Pre-Service Mathematics Teachers’ Concept Images - Hilmi Karaca (e-Kafkas Eğitim Araştırmaları Dergisi)
Artificial intelligence (AI) and AI-based tools are becoming increasingly important in mathematics education due to their potential to enrich learning experiences, provide customized solutions, and increase the effectiveness of learning processes. This case study was conducted to examine the impact of AI-based tool experiences on pre-service mathematics teachers' (PMTs) mathematical concept images. As a result of the content analysis, the data were categorized under the themes of component, understanding, and association, and the changes in PMTs' concept images after their ChatGPT experiences were examined according to these themes. Although not always, the ChatGPT experience had an effect on PMTs' mathematical concept images in general. In particular, PMTs mentioned more components that are directly related to mathematical concepts, while associating related concepts with different terms decreased. However, there were partial transformations in the understandings of the concepts. While subjective knowledge of concepts decreased, objective and directly related knowledge increased and unnecessary repetitions decreased. In conclusion, ChatGPT experiences contributed to the development of concept images of PMTs, but this contribution was not at the same level for all concepts.